POSSIBILITIES OF SUPPORT OF SPECIAL NEEDS STUDENTS AT THE GRADUATION EXAM - CASE STUDY OF A STUDENT WITH ASPERGER SYNDROME FOCUSING ON THE MODIFICATION OF GRADUATION EXAM CONDITIONS - Schwarzová, Lucie (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the paper is the theoretical anchoring of the autism spectrum disorder focusing mainly on the Asperger syndrome, as well as the classification of disorders according to the International Statistical Classification of Diseases (ICD-10) and the Diagnostic and Statistical Manual (DSM-V). The paper contains an overview of the legal regulations related to the possible modifications of the common part of the graduation exam. The research part is based on qualitative methodology, it includes a case study. Based on an intentional selection (age and diagnosis), a student with Asperger syndrome was chosen for the case study, who applied at the educational support center for the modification of the graduation exam conditions. Regarding the data collection, the research methods included a semi-structured interview with the legal representatives (with the consent of the student of age), and a class teacher, and the study of the documents kept in the educational support center. The research part contains information on the personal and schooling history, as well as on the symptoms reflecting the diagnostic dyad. The conclusion offers an overview of the specific support measures provided to the student for the common part of the national graduation exam. The aim of the study is to explore whether the symptoms of the Asperger syndrome diagnosis reflected in the deficiencies at school may be fully compensated through the modification of the graduation exam conditions.